Solving Method for the Optimal Decision of Multi-Market Subjects in Dynamic Game Based on Quota System and Green Certificate Trading Policy - Ding, Tao; He, Yuankang; Sun, Yuge; Fan, Yuqi; Qu, Ming; Li, Yan; Liu, Ruifeng; Chen, Tianen (2021)
The invention provides a solving method for the optimal decision of multi-market subjects in dynamic game based on quota system and green certificate trading policy. Firstly, considering the quota index of electricity selling enterprises in the electricity market, under the quota system and green certificate trading policy, a new market trading structure is established, and based on this, the decision-making behavior of market subjects is analyzed; then, based on the supply process of green power and green certificate in the new trading architecture, a multi-market dynamic game model based on quota system and green certificate trading policy is designed, which can maximize the profit or utility of each market subject, including power generation enterprises, power sales enterprises and power users, and obtain the optimal decision under the multi-subject game equilibrium; finally, numerical results are used to analyze the impact of quota system and green certificate trading policy on the trading decisions of multi-market subjects. The method fully considers the actual situation that China's quota system policy requires quota index assessment for power sales enterprises, on this premise, it provides research ideas for quantitative analysis of the impact of quota system and green certificate trading policy on multi-subjects in electricity market, it has strong practical reference significance. -- r Green cetafei 4 0 esrl --- -- mar o ~0. ThRcosteof Bundlegreen C nventinal ecmkinio p aelecteity electricity C /Unboundpower antity power electricity --- J-- purchase in hasrisen --- power sales entcertificateeprenterprisesio . . I - Dlcsn The cost of makeng iausme electricity ofLsers purchase is Ketil power transmitted purchase downwards Retail s p strategy market Fig. 1 - 7000 tD a 500 250 -reen electricquantity 6000 Conventional electricity trading volume 0 0.05 0.1 0.15 0.2 Quota Cy Fig. 2